The Predictors of Diabetic Nephropathy in Adult Patient with Diabetes: Systematic Literature Review - Nurul Azizatunnisa; Amelia Kurniati; Dikha Ayu Kurnia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes is a type of chronic disease that progresses over time and can lead to various complications, one of which is diabetic nephropathy. The prevalence of kidney disorders in individuals with diabetes at a productive age in Indonesia is 4%, but only 0.6% have been diagnosed. This systematic review provide information about many factors affecting diabetic nephropathy, both physical and psychological factors in adult patient with diabetes. This systematic literature review utilizes several databases, i.e EBSCO, Oxford Journal, ProQuest, PubMed, Sage Journal, Science Direct, and Springer Link which published in the past five years (2019-2024). We used PICO in literature searching process, i.e. diabetic nephropathy (population), self-care OR family support OR risk factor OR primary assessment OR early warning signs (intervention), standard care (comparison), diabetic nephropathy OR diabetic kidney disease OR glomerulosclerosis, diabetic (outcome). Articles were selected based on inclusion and exclusion criteria and are presented using the PRISMA diagram. There were 10 relevant articles were identified. The sample size in this study was 7.892 from many health care areas from primary health care, outpatient clinic, and emergency department. Diabetic patients in this study include prediabetes, type 1 diabetes, and type 2 diabetes, DM ESRD and asymptomatic severe hypertension that potential to suffer kidney disfunction. The physical factors of diabetic nephropathy were body mass index (BMI), duration of diabetes diagnosis, vital signs, laboratory examination and comorbidity. Psychological factors include family support, self-care, diabetes control and education, Quality of Life (QoL) or Well-Being Index. There were six physical factors and four psychological factors that could be predictors of diabetic nephropathy.